Retention of primary molars: diagnosis, etiology, treatment and clinical case report - Marcelle Danelon; Nayara Gonçalves Emerenciano; Heitor Ceolin Araújo; Liliana Carolina Báez-Quintero; Francyenne Maira Castro Gonçalves; Sara Tiemi Felipe Akabane; Nathalia Tavella; Robson Frederico Cunha (Asociación Latinoamericana de Odontopediatría, 2019)
This study shows a clinical case report about the retention of primary molars, with the aim of describing diagnosis, etiology, clinical implications and treatment of this condition. Local, environmental or genetic etiologic factors may lead to retention of primary molars, interfering with the normal sequence of eruption of the premolars. A 12-year-old female patient attended the Pediatric Dentistry Clinic of the Faculty of Dentistry of Araçatuba (FOA / UNESP), complaining of pain and volumetric increase in the buccal region of the tooth 63 and a scenario of age-incompatible eruption chronological analysis of teeth 54/55, 64/65, 74/75, 84/85. Complementary examinations were performed to establish the diagnosis, which was defined as prolonged retention of deciduous molars. Therapeutic conduct was based on the extraction of teeth with prolonged retention, followed by clinical and radiographic control until the successors erupted. It is concluded that the early diagnosis and intervention for prolonged retention are of fundamental Latinoamericanaimportance to avoid occlusal complications.